2022
DOI: 10.1186/s12888-022-03794-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with readmissions of patients with severe mental disorders under treatment with antipsychotics

Abstract: Background The aim of this study was to assess the risk of readmission in patients with severe mental disorders, compare it between patients using different types of antipsychotics and determine risk factors for psychiatric readmission. Methods Medical records of a non-concurrent cohort of 625 patients with severe mental disorders (such as psychoses and severe mood disorders) who were first discharged from January to December 2012 (entry into the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
2
2
0
Order By: Relevance
“…In addition to drug factors, the results of our meta-analysis showed that disease-related factors such as problem behaviors of drug and alcohol abuse (OR = 1.77), duration and severity of illness (OR = 1.14) can also influence medication adherence to a large extent. This is consistent with the findings of several previous studies 41 , 45 , 46 . Also, lower income and quality of life (OR = 1.23), personal attributes including age, gender, and education (OR = 1.21), were all significant in the results of this meta-analysis and were among the risk factors for patient medication adherence.…”
Section: Discussionsupporting
confidence: 94%
“…In addition to drug factors, the results of our meta-analysis showed that disease-related factors such as problem behaviors of drug and alcohol abuse (OR = 1.77), duration and severity of illness (OR = 1.14) can also influence medication adherence to a large extent. This is consistent with the findings of several previous studies 41 , 45 , 46 . Also, lower income and quality of life (OR = 1.23), personal attributes including age, gender, and education (OR = 1.21), were all significant in the results of this meta-analysis and were among the risk factors for patient medication adherence.…”
Section: Discussionsupporting
confidence: 94%
“…The study of individual antipsychotics speci cally clozapine, a mother atypical antipsychotic has shown functional recovery better than counterparts and lowering refractory schizophrenia states while maintaining clinical symptoms-free states of the patients as reported in an Indian study (50). Schizophrenia refractoriness is associated with poor treatment outcomes such as poor functioning, where controlling relapses aids in modifying the outcomes as reported by Portela and colleagues in Brazil (2017), they found that atypical antipsychotics were a protective factor against readmissions and relapses and so coinciding with the nding of the current study ndings (52). The study participants who did not receive any form of psychotherapy as part of their treatment had higher odds of functional disability compared to those who got psychotherapy as a component of their treatment.…”
Section: Discussionsupporting
confidence: 88%
“…7 One of the greatest contributors to readmissions in patients with schizophrenia is adherence to treatment recommendations as one trial showed a 92% increase in readmissions over a 5-year time frame in nonadherent patients. 8 Continuous treatment with antipsychotic medications is recommended in patients with schizophrenia. Although oral medications are commonly used, long-acting injectable (LAI) antipsychotics offer an alternative that may improve adherence to treatment.…”
mentioning
confidence: 99%
“…Adults with serious mental illness have an elevated rate of 30-day readmissions, and patients with schizophrenia have the highest rate, followed by those with bipolar disorder 7 . One of the greatest contributors to readmissions in patients with schizophrenia is adherence to treatment recommendations as one trial showed a 92% increase in readmissions over a 5-year time frame in nonadherent patients 8 …”
mentioning
confidence: 99%